2021
DOI: 10.3390/s21123975
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Discrimination of Salbutamol from Its Excipients in VentolinTM at Nanoporous Gold Microdisc Arrays

Abstract: The emergence of specific drug–device combination products in the inhalable pharmaceutical industry demands more sophistication of device functionality in the form of an embedded sensing platform to increase patient safety and extend patent coverage. Controlling the nebuliser function at a miniaturised, integrated electrochemical sensing platform with rapid response time and supporting novel algorithms could deliver such a technology offering. Development of a nanoporous gold (NPG) electrochemical sensor capab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 97 publications
0
4
0
Order By: Relevance
“…Various analytical methods and techniques have been used to determine the above salbutamol, and isoxsuprine, in pure form and pharmaceutical dosage including spectrophotometric 6-9 , electrochemical techniques [10][11][12][13][14] and HPLC methods [15][16][17][18] . The aim of the present work is to develop a very simple, rapid, accurate, precise, sensitive and less time consuming quantitative determination of salbutamol and isoxsuprine in pure form and pharmaceutical dosage.…”
Section: Figure 2 Chemical Structure Of Isoxuprinementioning
confidence: 99%
“…Various analytical methods and techniques have been used to determine the above salbutamol, and isoxsuprine, in pure form and pharmaceutical dosage including spectrophotometric 6-9 , electrochemical techniques [10][11][12][13][14] and HPLC methods [15][16][17][18] . The aim of the present work is to develop a very simple, rapid, accurate, precise, sensitive and less time consuming quantitative determination of salbutamol and isoxsuprine in pure form and pharmaceutical dosage.…”
Section: Figure 2 Chemical Structure Of Isoxuprinementioning
confidence: 99%
“…Nagle et al [11] present the development of a nanoporous gold (NPG) electrochemical sensor, capable of creating a unique fingerprint signal generated by inhalable pharmaceuticals, which provided the impetus for a study on the electrooxidation of salbutamol, the active bronchodilatory ingredient in Ventolin TM formulations. It was demonstrated that, in NPG-modified microdisc electrode arrays, salbutamol is distinguishable from the chloride excipient present at 0.0154 M using linear sweep voltammetry, and can be detected amperometrically.…”
Section: Micro and Nano Sensorsmentioning
confidence: 99%
“…Salbutamol sulfate is the active pharmaceutical ingredient (API) in several commercially available quick-relief medication formulations. It is available under several brand names, including Ventolin TM [65]. The reason for using ventolin syrup as a source of Salbutamol is its easy availability.…”
Section: Introductionmentioning
confidence: 99%